Crizotinib inhibits migration and expression of ID1 in MET-positive lung cancer cells: implications for MET targeting in oncology. (February 2014) - Stutz, Emanuel; Gautschi, Oliver; Fey, Martin F; Gugger, Mathias; Tschan, Mario P; Rothschild, Sacha I
ABSTRACT Aims: ID1 is an important component of the MET–SRC signaling pathway, which is a regulator of cell migration and invasion. We hypothesized that the ALK/MET inhibitor crizotinib inhibits migration via MET–SRC–ID1, rather than ALK.Materials & methods: We used ALK fusion-positive and -negative lung cancer cell lines; crizotinib, PHA-665752, and saracatinib, and stable transfection with shMET. We performed western blotting for p-ALK, ALK, p-MET, MET, p-SRC, SRC and ID1, and quantitative real-time PCR for ID1 .Results: Crizotinib decreased p-MET, p-SRC and ID1 levels in ALK- and or MET-positive cell lines and inhibited cell migration. Knockdown of MET was comparable with the effect of crizotinib.Conclusion: The effects of crizotinib on ID1 expression and cancer cell migration were associated with the presence of activated MET, rather than ALK fusion.